Experimental evaluation and thermodynamic modelling of AILs alkyl chain elongation on methane riched gas hydrate system - Khan, M.S. (Elsevier B.V., 2018)
In this study, the thermodynamic inhibition of CH4 rich binary mixed hydrate system (70-30 mol CH4 + CO2) is reported for four ammonium based ionic liquids (AILs) via experimental and modelling approaches. The T-cycle technique applied for the characterization of the AILs namely tetramethylammonium hydroxide (TMAOH), tetraethylammonium hydroxide (TEAOH), tetrapropyl ammonium hydroxide (TPrAOH) and tetrabutylammonium hydroxide (TBAOH). The hydrate liquid-vapour equilibrium (HLwVE) conditions of studied systems measure within the temperature and pressure ranges of 275.0â286.0 K and 3.0â7.50 MPa respectively at 10 wt aqueous AILs solutions. All the studied AILs except TBAOH inflicted the THI influence by shifting the HLwVE of CH4 enrich mixed gas hydrates. Elongation in AILs alkyl chain length attributed to decrease the average hydrate suppression temperature (ÎÅ¦). At 10 wt, TMAOH exhibited the maximum inhibition impact with a ÎÅ¦ value of 1.28 K, followed by TEAOH (0.8 K), TPrAOH (0.7 K), and TBAOH (â0.84 K) respectively. Instead of hydrate inhibitor, TBAOH worked as gas hydrate promotor owing to the presence of relatively higher alkyl chain cation (butyl) make it semi-clathrate hydrate. The study further extended for different concentrations (1, 5 and 10 wt) of TMAOH among the best considered AIL in this study. COSMO-RS investigation is also incorporated to further understand the thermodynamic inhibition behaviour of AILs via sigma profile analysis. Additionally, the enthalpies of hydrate dissociation for all studied AILs systems also calculated via Clausius-Clapeyron equation in this study. The calculated hydrate dissociation enthalpies data revealed that all the studied AILs except TBAOH show insignificant participation in mixed gas hydrate cage formation, therefore, do not form semi-clathrate hydrates. However, enthalpy data of TBAOH revealed that it participated in hydrate crystalline structure, therefore, worked as semi-clathrate hydrate. Furthermore, the HLwVE predictions of studied systems also performed via electrolyte based model proposed by Dickens and Quinby-Hunt and found in respectable agreement with the experimental data. Â© 2018 Elsevier B.V.